Comparative study of lipidic profile and blood pressure in lean and overweight dogs - Garaycochea C., Silvana (2018)
The aim of the present study was to compare levels of cholesterol, triglycerides, and blood pressure in canines. A total of 60 dogs were used (30 were lean and 30 were overweight). The animals were patients from the Clinic of Small Animals of the Faculty of Veterinary Medicine of the National University of San Marcos and were free of heart diseases. Blood samples were collected and processed by photocolorimetry in a chemical analyzer and the blood pressure measurement was done with a digital blood pressure monitor. The results showed hypertriglyceridemia in 16.7% of the overweight group, while 46.7% of the lean group and 90% of the overweight group showed hypercholesterolemia. In addition, 20 and 50% of the lean and overweight group respectively had high blood pressure values. Triglyceride and cholesterol levels were significantly higher in the overweight group (p<0.05), whereas there were no differences in systolic blood pressure values. There was an association between lean and overweight dogs with triglycerides and cholesterol.